POLA BAHASA GENERASI Z DI LINGKUNGAN UNIVERSITAS TADULAKO - Wulandari Wulandari; Asrianti Asrianti (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to describe the linguistic patterns of Generation Z within the academic environment of Tadulako University. The term "linguistic patterns" refers to habitual language usage employed in daily interactions, encompassing both academic and non-academic domains. The study adopts a descriptive qualitative method with a sociolinguistic approach. The data source consists of students categorized as Generation Z—those born between 1997 and 2012—who are currently active members of the academic community at Tadulako University. Data were collected through audio recordings, participatory observation, and non-participatory listening techniques. The data analysis was conducted using Miles and Huberman’s (2014) interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal three dominant linguistic patterns among Generation Z in the university setting: code-mixing (46.67%), interference (40%), and code-switching (13.33%). Code-mixing frequently occurs through the insertion of regional and foreign language elements (particularly English) into Indonesian, both in face-to-face interactions and on social media platforms. Interference is observed at the morphological level, such as the inappropriate use of affixation not conforming to standard Indonesian grammar, and at the syntactic level, where sentence structures are influenced by the speakers’ first language. Meanwhile, code-switching manifests in interlingual transitions within informal contexts, functioning as a communicative strategy to align with the interlocutor or to express group identity and solidarity. These findings indicate that the linguistic behavior of Generation Z at Tadulako University is shaped by a complex interplay of cultural background, social environment, and the influence of evolving communication technologies.